Preparation of metal‐phosphorus hybridized nanomaterials and the action of metal centers on the flame retardancy of epoxy resin. Issue 48 (23rd August 2017) - Liu, Lili; Huang, Yawen; Yang, Yu; Ma, Jiajun; Yang, Junxiao; Yin, Qiang
ABSTRACT: The action of metals on the flame retardancy of thermoplastic has aroused much interest in recent years. However, their action on thermosets is still not clear. In this work, metal‐phosphorus hybridized nanomaterials with different metal centers were prepared via hydrothermal reaction between metal hydroxide/salts with phosphinic/phosphonic acids. The loading of these hybrids in epoxy (EP) resins resulted in great change on fire resistance. Thermogravimetric analysis, solid and gas phase analysis results indicated that the flame retardant action of the hybrids perhaps didn't take place following the conventional models in condensed and gas phase. It was found that the flame retardancy was greatly correlated with the action of metal centers with EP resin, which resulted in the formation of metal‐oxygen bonds and the delayed release of flammable compounds from EP resin. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45445. Abstract :